Double-embedded microcapsule powder as well as formula, preparation method and application thereof

Through the method of combining proteins and polysaccharide wall materials, double embedding of core materials of different polarity is achieved, solving the problems of low embedding efficiency and insufficient safety in the existing technology, and improving stability and biocompatibility is achieved. It is suitable for food, medicine, cosmetics and other fields.

CN120323646APending Publication Date: 2025-07-18INNOBIO CORP LTD

Patent Information

Application Number
CN202510566553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively embed core materials of different polarities at the same time, and a large number of organic solvents are used during the preparation process, which leads to difficulties in industrial expansion of production and is difficult to meet the safety requirements in the fields of food and medicine.

Method used

The combination of proteins and polysaccharide wall materials is adopted to achieve double embedding of hydrophilic, lipophilic, amphiphilic and amphoteric insoluble core materials through the fine regulation of the agglomeration process and spray drying, thereby enhancing the stability and biocompatibility of the microcapsules and avoiding the use of organic solvents.

Benefits of technology

It realizes diversified compatibility of core materials of different polarity in the same microcapsule, enhances the stability of the microcapsule and its ability to isolate the external environmental impact, is suitable for industrial production, and is suitable for food, medicine and cosmetics fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120323646A_ABST
    Figure CN120323646A_ABST
Patent Text Reader

Abstract

The invention discloses double-embedded microcapsule powder as well as a formula, a preparation method and application thereof, and belongs to the technical field of foods. According to the invention, phase condensation is carried out on core materials with different polarities, so that microcapsule powder capable of pairwise embedding the core materials with different polarities, lipophilic core materials such as vegetable oil (conjugated linoleic acid glyceride, medium chain triglyceride, DHA algal oil, linseed oil, sunflower seed oil and the like), animal oil, haematococcus pluvialis oil or fat-soluble vitamins and the like are obtained; the hydrophilic core materials comprise water-soluble vitamins, high-solubility amino acids and the like, the amphiphilic core materials comprise diglyceride oil, phospholipid oil, sugar fat oil and the like, and the amphoteric insoluble core materials comprise polyphenol substances or low-solubility amino acid substances and the like. According to the microcapsule powder and the preparation method thereof, diversification and compatibility of properties of the core material are realized, the corresponding microcapsule powder effectively isolates negative effects of external environmental factors such as oxygen, moisture, illumination and temperature change on the core material, and the microcapsule powder can be widely applied to industries such as medicine, food and cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microcapsule powder, and particularly relates to a double-embedded microcapsule powder and its formulation, preparation method and application. Background Art

[0002] Microencapsulation technology is a technology that encapsulates solid, liquid or gaseous substances in tiny capsules. These capsules usually have one or more layers of thin films, which can protect the encapsulated substances from the influence of the external environment and at the same time control their release rate and mode. Microencapsulation technology has been widely used in many fields such as food, medicine, cosmetics, and agriculture.

[0003] Traditional microencapsulation technologies are often designed for a certain type of core material with a specific polarity, and it is difficult to meet the encapsulation requirements of different polar core materials at the same time. For example, the microencapsulation method designed for hydrophilic core materials may not be able to effectively encapsulate lipophilic core materials, and vice versa. In addition, for the encapsulation of amphiphilic or amphiphobic insoluble core materials, traditional methods often have problems such as low encapsulation efficiency and poor stability.

[0004] To overcome the limitations of traditional microencapsulation techniques, a microcapsule powder technology capable of double encapsulation is required. A series of research results on the double encapsulation of different polar core materials in microcapsule powder are recorded in the prior art: CN112205628A discloses such a technical solution: by stirring and dissolving raw materials such as zein, chitosan, curcumin, and quercetin to ensure uniform mixing. Subsequently, ethanol is removed by rotary heating, and the pH value is adjusted to form a complex coacervate with double encapsulation function, successfully achieving the double encapsulation of active ingredients such as curcumin and quercetin. However, a large amount of organic solvents are introduced during the preparation process, resulting in excessive residual solvents, and the overall process is not suitable for large-scale production. CN202323544959.5 discloses such a technical solution: by designing a microfluidic chip, the chip includes a first chip and a second chip. Through specific flow channel design and fluid control, water-in-oil-in-water structured microdroplets or oil-in-water-in-oil structured microdroplets can be prepared, realizing the efficient preparation of double-encapsulated structured microdroplets, and the automation degree of the preparation process is high. However, at present, the chip preparation and operation process are relatively complex, requiring professional skills and equipment support, and the stability and biocompatibility of the microdroplets need to be further evaluated and optimized. CN101214219A discloses such a technical solution: using food-grade vitamin A as the core material of the nanosphere and monoglyceride or beeswax as the wall material of the nanosphere to prepare a nanosphere suspension. Subsequently, vitamin E and the nanosphere suspension are used together as the core material of the microsphere, and octenyl succinic acid esterified starch containing Tween-80 is used as the wall material of the microsphere. A nanosphere / microsphere double-encapsulation system is prepared by thermal homogenization followed by spray drying, realizing the simultaneous encapsulation of vitamin A and vitamin E and improving their stability and bioavailability. In addition, CN201310066779.5 discloses such a technical solution: using liposomes composed of phospholipids, cholesterol, PEG-modified phospholipids, and water-soluble drugs, the water-soluble drugs are encapsulated in the aqueous phase of the liposome, and at the same time, lipophilic drugs can also be encapsulated in the membrane of the liposome. The simultaneous encapsulation of water-soluble drugs and lipophilic drugs is realized. Liposomes, as a commonly used drug carrier, have good biocompatibility and safety. These patents all disclose the preparation methods of microcapsule powder with double encapsulation of different polar core materials. However, most of them rely on technologies that are not yet fully mature at the laboratory stage, or use a large amount of organic solvents during the preparation process, resulting in limitations of these technologies in actual production and industrial expansion, and it is also difficult to meet the strict requirements for safety in fields such as food and medicine. To break through the bottleneck of the existing technology, future research must focus on achieving an optimized preparation process aimed at industrial transformation. In addition, the usage amount of organic solvents must be strictly controlled to reduce residual solvents, thereby ensuring the safety of the product. To overcome the limitations of the existing technology, the future research direction must be able to achieve an optimized preparation process aimed at industrial transformation, and improve the stability and biocompatibility of the microcapsule powder.And prevent organic reagents and excessive residual solvents to achieve safe application in more fields such as food, medicine, cosmetics, etc.

[0005] In summary, although the preparation of double-embedded microcapsule powder has been achieved in the prior art, there are still many technical problems to be solved. Future research directions should focus on optimizing the preparation process, improving the stability and biocompatibility of microcapsule powder, and expanding application fields to meet more needs. Summary of the Invention

[0006] To solve the problems in the background art, the present invention aims to provide double-embedded microcapsule powder and its formulation, preparation method and application. By finely regulating the agglomerated particles, controlling the reaction parameters of the agglomeration process, judging the crosslinking degree of the curing process, and adjusting the final spray drying and other key steps, the present invention realizes the effective encapsulation of hydrophilic core materials, lipophilic core materials, amphiphilic core materials and amphoteric insoluble core materials, and combines protein-based and polysaccharide-based double wall materials, which not only enhances the mechanical strength of the microcapsules, but also improves their resistance to the external environment (such as oxygen, moisture, light, temperature), ensuring the stability of the microcapsules and the reliability of downstream applications. This method enables different nutritional components to be encapsulated in the same microcapsule at the same time, realizing the diversification and compatibility of the core material properties, effectively isolating the negative impact of external factors on the core material, and maintaining excellent stability even in a humid environment. Considering the requirements of subsequent production and practical applications, the present invention selects specific combinations of raw materials and auxiliary materials and process steps to ensure the high efficiency of the production process and the high quality of the product, and can be widely applied to industries such as medicine, food and cosmetics, providing a more stable and efficient solution.

[0007] First, the first aspect of the present invention protects a formulation of double-embedded microcapsule powder, which comprises the following components in parts by weight:

[0008] 5-60 parts of core material in group A, 5-40 parts of core material in group B, 5-16 parts by weight of protein-based wall material, 3-19 parts by weight of polysaccharide-based wall material, 0.1-2 parts by weight of curing enzyme, 1-10 parts of filler, 1-4 parts of pH regulator, 0-2 parts by weight of antioxidant.

[0009] For the above technical solution, the core material in group A is various lipophilic core materials, amphiphilic core materials or amphoteric insoluble core materials;

[0010] More preferably, the lipophilic core material includes various vegetable oils, such as linseed oil, safflower oil, perilla seed oil, camellia seed oil, sunflower oil, high-oleic sunflower oil, sea buckthorn seed oil, soybean oil, pumpkin seed oil, pine seed oil, sea buckthorn fruit oil, peony seed oil, coconut oil, walnut oil, hickory oil, olive oil, hemp seed oil, wheat germ oil, grape seed oil, rapeseed oil, palm oil, conjugated linoleic acid, conjugated linoleic acid glyceride, medium-chain triglyceride, silybum marianum seed oil; or Haematococcus pluvialis oil (astaxanthin oil); or various animal oils, fresh cream, butter, anhydrous butter, fish oil, etc.; or various fat-soluble vitamins, such as vitamin A, vitamin B, vitamin D, vitamin E (d-α tocopherol, dl-α tocopherol, mixed tocopherols), vitamin K, etc., or a mixture of one or more of them; the addition amount of the lipophilic core material is preferably 30-55 parts by weight, more preferably 35-53 parts by weight; the optimal range is 40-50 parts by weight.

[0011] More preferably, the amphiphilic core material includes various diglyceride oils, such as linseed diglyceride oil, peanut diglyceride oil, corn diglyceride oil, rapeseed diglyceride oil, coconut diglyceride oil, palm diglyceride oil, rice diglyceride oil, soybean diglyceride oil, sunflower diglyceride oil, pumpkin diglyceride oil, tomato diglyceride oil, safflower diglyceride oil, perilla seed diglyceride oil (perilla seed diglyceride oil, perilla seed diglyceride oil), camellia seed diglyceride oil, high-oleic sunflower diglyceride oil, sea buckthorn seed diglyceride oil, pumpkin seed diglyceride oil, pine seed diglyceride oil, sea buckthorn fruit diglyceride oil, peony seed diglyceride oil, walnut diglyceride oil, olive diglyceride oil, hemp seed diglyceride oil (cannabis seed diglyceride oil), wheat germ diglyceride oil, grape seed diglyceride oil, rapeseed diglyceride oil, palm diglyceride oil, silybum marianum seed diglyceride oil, etc.; and various phospholipid oils such as sunflower phospholipid, soybean phospholipid, etc., krill oil, egg yolk oil, phospholipid algal oil, etc.; and various glycolipid oils such as oat oil, rice bran oil, etc.; and a mixture of one or more of them; the addition amount of the amphiphilic core material is preferably 8-35 parts by weight, more preferably 9-30 parts by weight; the optimal range is 10-20 parts by weight.

[0012] More preferably, the amphoteric insoluble core material includes various polyphenolic substances, such as curcumin, quercetin, rutin, resveratrol, etc., and the addition amount of the amphoteric insoluble core material is preferably 6-30 parts by weight, more preferably 7-25 parts by weight; the optimal range is 8-15 parts by weight.

[0013] For the above-described technical solution, preferably, the core materials in Group B are hydrophilic core materials, amphiphilic core materials or amphoteric insoluble core materials; more preferably, the hydrophilic core materials include various water-soluble vitamins: ascorbic acid, sodium ascorbate, vitamin B group (vitamin B1, vitamin B2, vitamin B3, vitamin B5, vitamin B6, vitamin B7, vitamin B1), adenine, choline, inositol, etc.; and various highly soluble amino acids, which have high solubility in water, such as lysine, arginine, proline, hydroxyproline, glycine, alanine, β-alanine, valine, serine, threonine, cysteine, citrulline, L-glutamine, γ-aminobutyric acid, etc., and a mixture of one or more of them. The addition amount of the hydrophilic core material is preferably 8-40 parts by weight, more preferably 10-35 parts by weight; the optimal range is 12-30 parts by weight.

[0014] More preferably, the amphiphilic core materials include various diglyceride oils, such as linseed diglyceride oil, peanut diglyceride oil, corn diglyceride oil, rapeseed diglyceride oil, coconut diglyceride oil, palm diglyceride oil, rice diglyceride oil, soybean diglyceride oil, sunflower diglyceride oil, pumpkin seed diglyceride oil, tomato seed diglyceride oil, safflower diglyceride oil, perilla seed diglyceride oil (perilla seed diglyceride oil, perilla seed diglyceride oil), camellia seed diglyceride oil, high oleic sunflower diglyceride oil, seabuckthorn seed diglyceride oil, pumpkin seed diglyceride oil, pine nut diglyceride oil, seabuckthorn fruit diglyceride oil, peony seed diglyceride oil, walnut diglyceride oil, olive diglyceride oil, hemp seed diglyceride oil (cannabis seed diglyceride oil), wheat germ diglyceride oil, grape seed diglyceride oil, rapeseed diglyceride oil, palm diglyceride oil, silybum marianum seed diglyceride oil, etc.; and various phospholipid oils such as sunflower phospholipid, soybean phospholipid, etc., krill oil, egg yolk oil, phospholipid algal oil, etc.; and various glycolipid oils such as oat oil, rice bran oil, etc.; and a mixture of one or more of them; the addition amount of the amphiphilic core material is preferably 8-35 parts by weight, more preferably 9-30 parts by weight; the optimal range is 10-20 parts by weight.

[0015] More preferably, the amphoteric insoluble core materials include various polyphenol substances, such as curcumin, quercetin, rutin, resveratrol, etc., and various low solubility amino acids, which have low solubility in water, such as leucine, cystine, tyrosine, aspartic acid, glutamic acid, tryptophan, threonine, leucine, phenylalanine, methionine, isoleucine, histidine, etc. The addition amount of the amphoteric insoluble core material is preferably 6-30 parts by weight, more preferably 7-25 parts by weight; the optimal range is 8-15 parts by weight.

[0016] An important feature of the present invention is that by using a combination of protein-based wall materials and polysaccharide-based wall materials, effective encapsulation of hydrophilic core materials, lipophilic core materials, amphiphilic core materials, and amphiphobic insoluble core materials has been successfully achieved. That is to say, the core materials in Group A and Group B can have different polarities, thus ensuring that nutritional components with different properties can coexist in the same microcapsule, achieving the diversification and compatibility of the properties of the core materials.

[0017] For the above-mentioned technical solution, preferably, the protein-based wall materials mainly refer to one or a mixture of several of fish gelatin, porcine gelatin, bovine gelatin, soy protein, pea protein, pumpkin protein, hemp protein, chickpea protein, and barley protein; the addition amount of the protein-based wall materials is preferably 6-14 parts by weight, more preferably 8-13 parts by weight, and the optimal range is 9-11 parts by weight.

[0018] For the above-mentioned technical solution, preferably, the molecular weight of the protein-based wall materials is 50-250 kDa, more preferably the molecular weight is 60-220 kDa, and the optimal molecular weight is 70-195 kDa.

[0019] For the above-mentioned technical solution, preferably, the polysaccharide-based wall materials are mainly selected from one or a mixture of several of gum arabic, sodium alginate, alginate, chitosan, carrageenan, pectin, starch, modified starch, cellulose, methylcellulose, ethylcellulose, and carboxymethylcellulose; the addition amount of the polysaccharide-based wall materials is preferably 4-18 parts by weight, more preferably 8-17 parts by weight; the optimal range is 9-14 parts by weight.

[0020] For the above-mentioned technical solution, preferably, the fillers include one or a mixture of several of glucose syrup, lactose, maltose, solid corn syrup, and maltodextrin; the addition amount of the fillers is 3-9 parts by weight, and the optimal range is 5-7 parts by weight.

[0021] For the above-mentioned technical solution, preferably, the DE value of the fillers is 40-70, more preferably the DE value is 55-65, and the optimal DE value is 50-60.

[0022] For the above-mentioned technical solution, preferably, the immobilized enzyme mainly refers to transglutaminase; the addition amount of the immobilized enzyme is preferably 0.2-1.5 parts by weight, more preferably 0.3-1.2 parts by weight; the optimal range is 0.5-1.0 parts by weight.

[0023] For the above-described technical solution, preferably, the antioxidant is selected from one or a mixture of several of d-α tocopherol, dl-α tocopherol, mixed tocopherols, rosemary extract, phospholipids, butylated hydroxyanisole, antioxidant 264, and tert-butylhydroquinone. Further preferably, it is a mixture of one or several of mixed tocopherols, antioxidant 264, rosemary extract, phospholipids or butylated hydroxyanisole; the addition amount of the antioxidant is 0-2 parts by weight; more preferably 0.02-1.0 parts by weight; most preferably 0.1-0.2 parts by weight.

[0024] The rosemary extract is prepared according to the "National Food Safety Standard Food Additive Rosemary Extract GB 1886.172-2016", which is a food additive rosemary extract produced from the stems and leaves of rosemary through processes such as solvent extraction or supercritical carbon dioxide extraction and refining. The extraction solvents are water, methanol, ethanol, acetone and / or n-hexane, and the total antioxidant components (calculated as carnosic acid and carnosol) are ≥10%.

[0025] For the above-described technical solution, preferably, the pH regulator includes an acidic regulator and a basic regulator. Among them, the acidic regulator is selected from one or a mixture of several of citric acid, sulfuric acid, hydrochloric acid, phosphoric acid, and malic acid, with citric acid and phosphoric acid being preferred; the basic regulator is selected from one or a mixture of several of sodium hydroxide, sodium carbonate, potassium hydroxide, etc., with sodium hydroxide being preferred.

[0026] Another aspect of the present invention lies in protecting a method for preparing microcapsule powder using the above-described formula, including the following steps:

[0027] (1) Fully dissolve the protein-based wall material in 50-150 parts by weight of water;

[0028] (2) Fully dissolve the polysaccharide-based wall material in 30-190 parts by weight of water;

[0029] (3) Thoroughly mix the liquids prepared in steps (1) and (2);

[0030] (4) Add 0-1 part by weight of the antioxidant to the core material in group A and mix well;

[0031] (5) Mix 30-70% by weight of the liquid prepared in step (3) and the liquid prepared in step (4), and shear and emulsify at a rotation speed of 5000-9000 rmp; preferably 55-65% of the total weight

[0032] (6) Add 0-1 part by weight of the antioxidant to the core material in group B;

[0033] (7) The remainder of the liquid prepared in step (3) is mixed with the liquid prepared in step (6), and shear emulsification is carried out at a rotational speed of 5000 - 9000 rmp;

[0034] (8) Take the concentrated emulsion prepared in step (5), dilute it to a solid content of 4 - 7 wt%, then adjust the pH of the emulsion to 5.0 - 5.2, more preferably 5.10 - 5.15, adjust the particle size D90 of the system to 2 - 20 μm, cool it, add a curing enzyme for curing to form the first layer of multi-core microcapsules; inactivate the curing enzyme; the further preferred particle size D90 is 3 - 18 μm, and the most preferred particle size D90 is 4 - 15 μm;

[0035] (9) Take the concentrated emulsion prepared in step (7), pour it into the emulsion in step (8), adjust the pH to 4.4 - 4.5, more preferably 4.43 - 4.48, adjust the particle size D90 of the system to 20 - 50 μm, cool it, add a curing enzyme for curing to form the second layer of multi-core microcapsules; inactivate the curing enzyme; among them, the further more preferred particle size D90 is 30 - 40 μm, and the optimal particle size D90 is 35 - 40 μm;

[0036] The total amount of the curing enzyme in steps (8) - (9) is 0.1 - 2 parts by weight; the curing enzyme used in step (8) is 50 - 60% of the total weight; the remaining curing enzyme is used in step (9);

[0037] (10) Add a filler to (9), stir until completely dissolved, and then carry out spray drying to obtain the final product; among them, control the DE value of the filler to be 40 - 70, the further more preferred DE value is 45 - 65, and the optimal DE value is 50 - 60.

[0038] In steps (8) and (9), the curing enzyme uses a commercial off-the-shelf product; the curing process is to heat the emulsion containing the curing enzyme to 50 - 55 °C and keep it for 2 - 3 hours to complete the curing. The standard for the completion of curing is to heat it up to 90 - 95 °C again and keep it for 20 - 30 minutes, and there is no obvious rupture in the microcapsule shell layer.

[0039] Another aspect of the present invention is to protect a double-embedded microcapsule powder prepared by the method described above, which is a double-embedded microcapsule powder of multi-layer multi-core long-chain polyunsaturated fats with high barrier and anti-crushing properties; it also includes a core material group A and a core group B with different polarities. The particle size D90 of the first layer of multi-core microcapsules is 2 - 20 μm, preferably 3 - 18 μm, and the most preferred particle size D90 is 4 - 15 μm; the particle size D90 of the second layer of multi-core microcapsules is 20 - 50 μm, preferably 30 - 40 μm, and the optimal particle size D90 is 35 - 40 μm.

[0040] The last aspect of the present invention is to protect the application of the microcapsule powder described above in foods or health products.

[0041] More preferably, the applications include fields such as tablets, powders, candies, gummies, soft capsules, bread baking, milk powder, yogurt, liquid beverages, solid beverages, energy bars, cheese, complementary foods, various sauces, and ice cream.

[0042] Advantages of the present invention:

[0043] Diversification and compatibility:

[0044] Through specific combinations of raw and auxiliary materials and process steps, the preparation of double-embedded microcapsule powder for different polar core materials (such as hydrophilic core materials, lipophilic core materials, amphiphilic core materials, and amphoteric insoluble core materials) is achieved, enabling different nutritional components to be encapsulated in the same microcapsule simultaneously, significantly enhancing the diversification and compatibility of the product.

[0045] Enhanced stability:

[0046] The microcapsule powder can effectively isolate the negative effects of external environmental factors (such as oxygen, moisture, light, and temperature changes) on the core material, maintaining excellent stability even in a humid environment. This not only extends the shelf life of the product but also ensures the effectiveness and safety of the active ingredients.

[0047] Optimized production process:

[0048] The key steps of the present invention include the separate preparation processes of different polar core material condensed phases, fine regulation of condensed particles, reaction parameters during the condensation process, crosslinking degree during the curing process, and final spray drying. These steps ensure the consistency and controllability of product quality and are suitable for large-scale industrial production.

[0049] Environmentally friendly:

[0050] The process design avoids pollution situations such as organic reagents, reduces the use of chemical additives, and meets the requirements of green production and environmental protection. In addition, the production process is simplified, production costs are reduced, and economic benefits are improved.

[0051] High encapsulation rate and low surface content:

[0052] Experimental results show that the microcapsule powder prepared by the method of the present invention has excellent encapsulation rate and low surface content (≤2%), ensuring the effective protection and release performance of the core material, thereby enhancing the overall quality of the product.

[0053] Good tableting performance:

[0054] The prepared microencapsulated powder exhibits excellent hardness and friability during the tabletting process, ensuring the quality standards of tablets, including integrity and disintegration degree. It not only guarantees the effective dissolution of drug components but also avoids the phenomenon of loose tablets, facilitating subsequent coating, packaging, and transportation.

[0055] Widely applicable:

[0056] This microencapsulated powder can be widely applied in multiple fields, including but not limited to tablets, powders, candies, gummies, soft capsules, bread baking, milk powder, yogurt, liquid beverages, solid beverages, energy bars, cheese, complementary foods, various sauces, and ice cream, etc. This wide range of applicability provides more possibilities for product development. Description of the drawings

[0057] Figure 1 For Example 1: Using fish gelatin and gum arabic as wall materials, mixed tocopherols as antioxidants, algal oil DHA as lipophilic core material component A, and ascorbic acid as hydrophilic core material B. The figure shows microencapsulated particles with co-encapsulation of DHA and sodium ascorbate, demonstrating the feasibility of co-encapsulation of lipophilic core material components and hydrophilic core materials.

[0058] Figure 2 For Example 2: Using bovine gelatin and sodium carboxymethylcellulose as wall materials, antioxidant 264 as an antioxidant, linseed oil as lipophilic core material component A, and krill oil as amphiphilic core material B. The figure shows microencapsulated particles with co-encapsulation of linseed oil and krill oil, demonstrating the feasibility of co-encapsulation of lipophilic core material components and amphiphilic core material components.

[0059] Figure 3 For Example 3: Using soy protein and sodium alginate as wall materials, rosemary extract as an antioxidant, resveratrol as amphiphilic insoluble core material component A, and rapeseed oil diglyceride as amphiphilic core material B. The figure shows microencapsulated particles with co-encapsulation of resveratrol and rapeseed oil diglyceride, demonstrating the feasibility of co-encapsulation of amphiphilic insoluble core material components and amphiphilic core material components.

[0060] Figure 4 For Example 1: Scanning electron microscope (SEM) image of microencapsulated powder with fish gelatin - gum arabic composite wall material; showing the surface morphology of the microencapsulated powder prepared by the complex coacervation process in Example 1. A dense and pore-free structure can be seen, and no dissolution or hydrophilic pores appear, verifying its physical isolation performance for the core material.

[0061] Figure 5 : Scanning electron microscope (SEM) image of the dense surface structure of the complex coacervation wall material; showing the surface and structure of the microencapsulated powder, proving its density, no pores, and stability in water. Detailed implementation manners

[0062] The following non-limiting examples are used to further illustrate the technical solutions and effects of the present invention and should not be construed as any form of limitation to the content of the invention. Unless otherwise specified, the percentages in this specification are all mass percentages.

[0063] In the examples, for the product performance evaluation of samples, first, each sample is sampled and divided into several parallel samples; to ensure the scientificity and credibility of the product performance evaluation, the same number of multiple sub-samples are randomly selected for each product, and the evaluation is carried out using the same test conditions and measurement techniques, and the performance is quantified and compared through the statistical analysis (calculation of the average value) of the obtained data.

[0064] The rosemary extract described in the examples is prepared in accordance with "GB 1886.172-2016 National Food Safety Standard Food Additive Rosemary Extract", which is a food additive rosemary extract produced from the stems and leaves of rosemary through processes such as solvent extraction or supercritical carbon dioxide extraction and refining. The extraction solvents are water, methanol, ethanol, acetone, and / or n-hexane, and the total antioxidant components (calculated as carnosic acid and carnosol) are ≥10%.

[0065] Example 1

[0066] Weigh 90 g of water into a 500 mL beaker, with the water temperature at 60 °C. Add 11 g of fish gelatin to it. The average molecular weight of the fish gelatin used is 130 kDa, and stir at 150 rmp until completely dissolved. Then weigh 14 g of gum arabic into a 500 mL beaker, add 120 g of water, with the water temperature at 60 °C, and stir at 150 rmp until completely dissolved. Then pour the gelatin solution into the gum arabic aqueous solution and stir at 150 rmp for 20 minutes to obtain a wall material mixture. Weigh 50 g of algal oil DHA and 0.2 g of mixed tocopherols into a 200 mL beaker, heat in a water bath at 60 °C, and mix and stir evenly. This is the core material of Group A. Mix 60% of the wall material mixture with the core material of Group A, and shear and emulsify at 9000 rmp to obtain an emulsion of the core material of Group A. Pour it into a stirring kettle for dilution until the solid content concentration is 6%. Then use a 0.1% concentration hydrochloric acid dilution solution to adjust the pH of the emulsion to 5.1, adjust the particle size of the system to D90 of 6.0 μm, then cool to 15 °C, add 0.5 g of curing enzyme for curing, heat to 80 °C for 30 min to inactivate the curing enzyme, and then cool to 60 °C to obtain the first layer of multi-core microcapsules; weigh 12 g of ascorbic acid into a 200 mL beaker. This is the core material of Group B. Dissolve the remaining core material of Group B in 40% of the wall material mixture and mix, and shear and emulsify at 5000 rmp to obtain a solution of the core material of Group B. Pour the component B into a stirring kettle for the above operations. After adjusting the pH to 4.5 with a 0.1% concentration hydrochloric acid dilution solution, the particle size is D90 of 36 μm. Then cool to 15 °C, add 0.5 g of curing enzyme for curing, heat to 80 °C for 30 min to inactivate the curing enzyme, and then cool to 60 °C to form the second layer of multi-core microcapsules. Finally, add 12 g of solid corn sugar syrup as a filler into the emulsion, with its DE value being 60. After dissolution, perform spray drying, with the inlet air temperature at 180 °C and the outlet air temperature at 85 °C to obtain the corresponding microcapsule powder. Then sieve and package the dried powder, and label it as Sample 1.

[0067] Example 2

[0068] Weigh 140 g of water into a 500 mL beaker, with the water temperature at 65 °C. Add 13 g of bovine gelatin to it. The average molecular weight of the bovine gelatin used is 195 kDa. Stir at 150 rmp until completely dissolved. Then weigh 17 g of sodium carboxymethylcellulose into a 500 mL beaker, add 80 mL of water, with the water temperature at 65 °C, and stir at 150 rmp until completely dissolved. Then pour the bovine gelatin solution into the sodium carboxymethylcellulose aqueous solution and stir at 150 rmp for 20 minutes to obtain the wall material mixture. Weigh 30 g of linseed oil and 0.02 g of antioxidant 264 into a 200 mL beaker, water bath at 55 °C, and mix and stir evenly. This is the core material of Group A. Mix 50% of the wall material mixture with the core material of Group A, and shear and emulsify at 8000 rmp to obtain the core material emulsion of Group A. Pour it into a stirring kettle for dilution until the solid content is diluted to 6% concentration. Then adjust the pH of the emulsion to 5.2 with a 0.1% concentration sulfuric acid dilution solution, adjust the particle size of the system to D90 of 4.0 μm, then cool to 15 °C, add 0.5 g of immobilized enzyme for curing, heat to 80 °C for 30 min to inactivate the immobilized enzyme, and then cool to 60 °C to obtain the first layer of multi-core microcapsules; weigh 20 g of krill oil and 0.02 g of antioxidant 264 into a 200 mL beaker, water bath at 40 °C, and mix and stir evenly. This is the core material of Group B. Dissolve the remaining core material of Group B in 50% of the wall material mixture and mix, shear and emulsify at 6000 rmp to obtain the core material solution of Group B. Pour the component B into a stirring kettle for the above operations, adjust the pH to 4.5 with a 0.1% concentration sulfuric acid dilution solution to obtain a particle size of D90 of 31 μm, then cool to 15 °C, add 0.5 g of immobilized enzyme for curing, heat to 80 °C for 30 min to inactivate the immobilized enzyme, and then cool to 60 °C to form the second layer of multi-core microcapsules. Finally, add 19 g of the filler glucose syrup with a DE value of 55 to the emulsion, dissolve it and then perform spray drying, with the inlet air temperature at 170 °C and the outlet air temperature at 75 °C to obtain the corresponding microcapsule powder, and perform screening and packaging on the dried powder, denoted as Sample 2.

[0069] Example 3

[0070] Weigh 140 g of water into a 500 mL beaker, with the water temperature at 55 °C. Add 14 g of soy protein to it. The average molecular weight of the soy protein used is 78 kDa, and stir at 150 rmp until completely dissolved. Then weigh 18 g of sodium alginate into a 500 mL beaker, add 170 mL of water, with the water temperature at 55 °C, and stir at 150 rmp until completely dissolved. Then pour the soy protein solution into the sodium alginate solution and stir at 150 rmp for 20 minutes to obtain the wall material mixture. Weigh 10 g of resveratrol and 0.07 g of rosemary extract into a 200 mL beaker. This is the core material of Group A. Disperse the core material of Group A in 40% of the wall material mixture and mix them, and shear and emulsify at 9000 rmp to obtain the core material mixture of Group A. Pour the core material mixture of Group A into a stirring kettle for dilution until the solid content concentration is 6%. Then adjust the pH of the emulsion to 5.0 with a 0.1% concentration phosphoric acid dilution solution, adjust the particle size of the system to D90 of 15.0 μm, then cool to 15 °C, add 1.0 g of curing enzyme for curing, heat to 80 °C for 30 min to inactivate the curing enzyme, and then cool to 60 °C to obtain the first layer of multi-core microcapsules; weigh 40 g of rapeseed diglyceride oil and 0.07 g of rosemary extract into a 200 mL beaker, water bath at 55 °C, mix and stir evenly. This is the core material of Group B. Mix the remaining 60% of the wall material mixture with the core material of Group A, adjust the pH to 4.4, and then the particle size is D90 of 39 μm. Then cool to 15 °C, add 0.5 g of curing enzyme for curing, heat to 80 °C for 30 min to inactivate the curing enzyme, and then cool to 60 °C to form the second layer of multi-core microcapsules. Finally, put 16 g of the filler maltose with a DE value of 50 into the emulsion, dissolve it and then spray dry it, with the inlet air temperature at 200 °C and the outlet air temperature at 90 °C to obtain the corresponding microcapsule powder, and then sieve and package the dried powder, denoted as Sample 3.

[0071] Example 4

[0072] Weigh 130 g of water into a 500 mL beaker. The water temperature is 55 °C. Add 14 g of casein to it. The average molecular weight of the casein used is 20 kDa. Stir at 150 rmp until completely dissolved. Then weigh 18 g of pectin into a 500 mL beaker, add 170 mL of water, with the water temperature at 55 °C, and stir at 150 rmp until completely dissolved. Then pour the casein solution into the pectin solution and stir at 150 rmp for 20 minutes to obtain the wall material mixture. Then weigh 30 g of astaxanthin oil and 0.1 g of sunflower phospholipids into a 200 mL beaker. This is the core material of Group A. Disperse the core material of Group A in 40% of the wall material mixture and mix, and shear and emulsify at 9000 rmp to obtain the core material mixture of Group A. Pour the core material mixture of Group A into a stirring kettle for dilution until the solid content concentration is 6%. Then adjust the pH of the emulsion to 5.0 with a 0.1% concentration phosphoric acid dilution solution, adjust the particle size of the system to D90 of 15.0 μm, then cool to 15 °C, add 1.0 g of curing enzyme for curing, and heat to 80 °C for 30 min to inactivate the curing enzyme and then cool to 60 °C to obtain the first layer of multi-core microcapsules; then weigh 20 g of γ-aminobutyric acid and 0.1 g of phospholipids into a 200 mL beaker, water bath at 55 °C, mix and stir evenly. This is the core material of Group B. Mix the remaining 60% of the wall material mixture with the core material of Group A, adjust the pH to 4.4 to obtain a particle size of D90 of 38 μm, then cool to 15 °C, add 0.5 g of curing enzyme for curing, and heat to 80 °C for 30 min to inactivate the curing enzyme and then cool to 60 °C to form the second layer of multi-core microcapsules. Finally, add 17 g of filler glucose syrup with a DE value of 55 into the emulsion, dissolve it and then perform spray drying, with the inlet air temperature of 200 °C and the outlet air temperature of 90 °C to obtain the corresponding microcapsule powder, and then screen and package the dried powder, denoted as Sample 4.

[0073] Example 1: Use fish gelatin and arabic gum as wall materials, mixed tocopherol as an antioxidant, algal oil DHA as the lipophilic core material component A, and ascorbic acid as the hydrophilic core material B. By using the method of separate emulsification and two-time acidification and coagulation, two-layer multi-core microcapsules with different polarities with a primary shell D90 of 6.0 μm and a secondary shell D90 of 36.0 μm are obtained, as Figure 1 .

[0074] Example 2: Use bovine gelatin and sodium carboxymethylcellulose as wall materials, antioxidant 264 as an antioxidant, linseed oil as the lipophilic core material component A, and krill oil as the amphiphilic core material B. By using the method of separate emulsification and two-time acidification and coagulation, two-layer multi-core microcapsules with different polarities with a primary shell D90 of 4.0 μm and a secondary shell D90 of 31.0 μm are obtained, as Figure 2 .

[0075] Example 3: Using soy protein and sodium alginate as wall materials, rosemary extract as an antioxidant, resveratrol as amphiphilic insoluble core material component A, and rapeseed diglyceride as amphiphilic core material B. After separate emulsification and two-step acid coagulation, a two-layer multi-core microcapsule with different polarities is obtained, where the D90 of the primary shell is 15.0 μm and the D90 of the secondary shell is 39.0 μm, as shown in Figure 3 .

[0076] Example 4: Using casein and pectin as wall materials, phospholipids as an antioxidant, astaxanthin oil (Haematococcus pluvialis oil) as lipophilic core material component A, and γ-aminobutyric acid as hydrophilic core material B. After separate emulsification and two-step acid coagulation, a two-layer multi-core microcapsule with different polarities is obtained, where the D90 of the primary shell is 15.0 μm and the D90 of the secondary shell is 38.0 μm.

[0077] From the perspective of the selection of wall materials, gelatin of animal origin was used in Examples 1 and 2, soy protein of plant origin was used in Example 3, and casein of animal origin was used in Example 4.

[0078] From the perspective of the selection of the two core materials, a combination of lipophilic and hydrophilic core materials was used in Examples 1 and 4, a combination of lipophilic and amphiphilic core materials was used in Example 2, and a combination of amphiphilic insoluble and amphiphilic core materials was used in Example 3. There are obvious differences in the polarities of the core materials with different components.

[0079] From the perspective of the selection of antioxidants, mixed tocopherols, antioxidant 264, and phospholipids were used in Examples 1, 2, and 4 respectively, all of which are common food-grade antioxidants; while rosemary extract, a natural antioxidant, was used in Example 3.

[0080] Example 5

[0081] The product performance of Sample 1, Sample 2, and Sample 3 was evaluated. The determination of the surface content can visually show the embedding rate of the two core materials. The lower the surface content, the better the embedding property. The calculation formula for the surface content is: Surface content % = Content % of a certain component extracted from the surface / Content % of a certain component in the raw material core material * 100% (taking DHA as an example, the DHA content on the product surface = Content % of docosahexaenoic acid component extracted from the surface / Content % of docosahexaenoic acid in the raw material DHA oil * 100%). Generally, it is considered that ≤ 2% indicates good embedding property; and a tableting experiment was carried out with a 5% content. After tableting, the tablet hardness was used as the evaluation index, which has obvious advantages for the integrity and disintegration degree of the tablets. If the hardness is too high, the drug and excipients are tightly bonded together, and the tablets are difficult to disintegrate, and the drug components cannot be effectively dissolved, ultimately affecting the curative effect. If the hardness is too low, it is difficult to ensure the integrity of the tablets, and phenomena such as loose tablets may occur, seriously affecting the subsequent processes of coating, packaging, and transportation. Generally, the optimal hardness range for tablets is 160 - 210 N; and the friability of the tablets reflects the anti-wear and vibration resistance ability of the tablets, and is also an important item for the quality standard inspection of the tablets. Generally, the weight loss should not exceed 1%, and no broken, cracked, or pulverized tablets should be detected, and the product is considered qualified. The final results of the overall test are shown in Table 1:

[0082] Table 1

[0083]

[0084] As can be seen from the results, the microcapsule powder with double embedding of different polar core materials obtained by the process disclosed in the present application has good appearance, taste, and smell, and the surface content of each component ≤ 2%. This proves that the present invention selects specific combinations of raw materials and excipients and process steps to obtain microcapsule powder with double embedding of two different polar core materials, such as hydrophilic core materials, lipophilic core materials, amphiphilic core materials, and amphoteric insoluble core materials, enabling different originally-natured nutritional components to be encapsulated in the same microcapsule at the same time, realizing the diversification and compatibility of the core material properties. And the tablet hardness is within the optimal range of 160 - 210 N, the friability ≤ 1%, and there is no crack or pulverized state, which can ensure the integrity and disintegration degree of the tablets, can ensure the effective dissolution of the drug components, and there will be no loose tablet phenomenon, and can ensure the subsequent processes of coating, packaging, and the preservation and transportation of the product.

[0085] Example 6

[0086] Samples 1, 2, and 3 were respectively divided into several parallel samples; they were respectively placed in an accelerated oven at 40°C and 75% humidity for three months for product stability evaluation. The degradation rate calculation formula is: Degradation rate % = (Initial content of the sample - Content of the sample after placement) / Initial content of a certain component in the sample * 100% (taking the DHA content as an example, DHA degradation rate % = (Content % of initial docosahexaenoic acid - Content % of docosahexaenoic acid in the sample after placement) / Initial content of docosahexaenoic acid in the sample * 100%). Other measurements were all carried out using national standards or industry standards. The results are shown in Table 2:

[0087] Table 2

[0088]

[0089]

[0090] It can be seen from the accelerated stability experiment in the thermostatic and humidified chamber that after 3 months of acceleration, the appearance, taste, and smell of the three samples did not show obvious rancid changes. Only a faint oily smell overflowed after 3 months of acceleration. Among them, the peroxide value and acid value increased slightly. Generally, it is considered that when the peroxide value after three months of acceleration is ≤ 10.0 meq / kg and the acid value is ≤ 1.0 mg KOH / g, the product has good stability. From the perspective of the product degradation rate, accelerating for 3 months can ensure that the degradation rate of each component is ≤ 5.0 meq / kg. It can be seen that the product prepared by the process of this application has a dense embedding, good barrier properties, and excellent heat resistance, antioxidant stability, and storage stability. In addition, the difference in the degradation rates of different core materials also reflects the consistency and reliability of the method of the present invention in treating various polar core materials, providing a solid foundation for the wide application of the product in the fields of medicine, food, cosmetics, etc.

[0091] Example 7

[0092] Based on the process of Example 1, without changing the original formula materials and their proportions, only the amount of acid added was changed. The influence of the particle size of the microcapsules during the formation of the first shell layer on the surface content of each component of the product, that is, the embedding effect performance, was mainly investigated. The product state is shown in Table 3:

[0093] Table 3

[0094]

[0095]

[0096] From the results, based on the process of Example 1, the product performance of the microcapsule powder can be affected by adjusting the particle size of the first shell layer. An appropriate particle size of the first shell layer can improve the embedding and tableting application performance of the product. However, too small or too large a particle size of the first shell layer will result in the failure of the preparation of the microcapsule powder or a decrease in product quality. The initial shell layer particle size D90 for preparing the multi-core multi-layer microcapsule layer must be between 2 - 20 μm. After cooling and adding solidifying enzyme for solidification, the first layer of multi-core microcapsules is formed. The further preferred particle size D90 is 3 - 18 μm, and the most preferred particle size D90 is 4 - 15 μm. If it is higher than the range, the final formed particle size will be too large, with a too large difference from the base powder particle size. After tableting, the hardness of the tablet and the anti-wear effect will be poor, and it is easy to leak oil after shearing, with an increase in surface content. When the particle size is even larger, there will be a phenomenon of sticky tower in spray drying, and the corresponding microcapsule powder cannot be obtained. While if the particle size is too small, cohesive particles cannot be formed or the subsequent layer cohesion cannot attach and grow, and finally no cohesive particles are formed. Moreover, if the particle size is too small, the surface area will be too large, and the embedding shell layer will be thinner, which will also affect the final embedding effect, and the surface content will increase significantly. For the sample with the initial shell layer particle size D90 of 4 - 10 μm, the initial surface oil is lower, its tableting hardness and friability are qualified, and the detected surface content is ≤2%, and the product is qualified. Therefore, it is necessary to be within the preferred range of the initial shell layer particle size D90 of 3 - 18 μm, and the most preferred particle size D90 of 4 - 15 μm to achieve the corresponding embedding and tableting performance effects.

[0097] Example 8

[0098] Based on the process of Example 1, without changing the original formula materials and proportions, the molecular weight of the protein-based wall material is adjusted, and the influence of the molecular weight of the protein-based wall material on the sample state is mainly investigated. The test results are shown in Table 5:

[0099] Table 4

[0100]

[0101]

[0102] In terms of the results, Samples 1, 2, and 3 all showed good appearance, taste, and smell, without obvious off-flavors. As the average molecular weight of the protein-based wall material decreased, the algal odor of the samples gradually increased, and the surface oil content also increased accordingly. In addition, when the average molecular weight of the protein-based wall material was too large, the powder viscosity would also increase, resulting in an obvious fishy smell. The molecular weight of the protein-based wall material was 50 - 250 kDa, more preferably 60 - 220 kDa, and most preferably 70 - 195 kDa. If it was lower than 50 kDa, the protein-phase emulsion was thinner, and there was an obvious layering during the emulsification process with the oil phase. Eventually, oil floating easily occurred during the embedding process, and the surface content of the product was higher. When the molecular weight was greater than 250 kDa, the viscosity was too high, which was not conducive to the formation of multi-core microcapsules. The microcapsule morphology was irregular, which would also affect the final embedding effect. For example, in Comparative Examples 9 - 11 and 14 - 16, they were evaluated by tabletting respectively, and the hardness of the tablets was too small, and the friability was relatively high ≥1%, and the products were unqualified. Therefore, the average molecular weight of the protein-based wall material must be within the range of 50 - 250 kDa (optimally 70 - 195 kDa) to ensure that the product has a good appearance and taste, while maintaining a low surface content and achieving the corresponding tabletting effect.

[0103] Example 9

[0104] Based on the process of Example 1, without changing the original formula materials and proportions, the DE value of the filler was adjusted, and the influence of the DE value on the sample state was mainly investigated. The test results are shown in Table 5:

[0105] Table 5

[0106]

[0107]

[0108] In terms of the results, the DE value of the filler had a certain influence on the sample state. As the DE value of the filler increased, the appearance, taste, and smell of Samples 1, 2, and 3 did not change significantly, but the surface content of the core material was slightly different. However, the DE value of the filler must be within the range of 40 - 70, more preferably 45 - 65, and most preferably 50 - 60. From the above table, we can find that when the DE value was too low <20, (such as in Comparative Examples 17 - 19), the viscosity of the dissolved sugars was too high, and the filling effect was poor, and pores were likely to appear, resulting in an increase in the surface content. Fillers with a higher DE value >70 were prone to caking and moisture absorption after spray drying, and the powder was sticky. Although the surface content was low, the powder state was poor, and the fishy smell overflowed, such as in Comparative Examples 21 and 22. Samples with a filler DE value within the range of 40 - 70 had a better powder state, good taste, and the surface content of each component was ≤2.0%, and the products were qualified.

[0109] Example 10

[0110] Based on the process of Example 1, without changing the formulation dosage and process parameters, only changing the dosage of the wall material, the influence of the wall material on the sample state was mainly investigated, and the test results are shown in Table 6:

[0111] Table 6

[0112]

[0113]

[0114] From the results, if the protein-based wall material is too high, obvious wire drawing will occur after spray drying, and the product state is not good. If the protein wall material is too low, the embedding effect is poor, and the surface content of the product is too high. If the polysaccharide-based wall material is too high, the powder will show a certain degree of adhesion. If the polysaccharide wall material is too low, the embedding effect is not good, the surface content of the product is too high, and the fishy smell overflows. For example, in Comparative Examples 21-23 and 29-31, the protein-based wall material is 5-16 parts by weight, and the polysaccharide-based wall material is 3-19 parts by weight, then the embedding effect is better, and the tablet hardness is within the best range of 160-210 N, the friability ≤ 1%, and there is no cracked crushing state, which can ensure the integrity and disintegration degree of the tablets, can not only ensure the effective dissolution of the drug components, but also prevent the phenomenon of loose tablets, and can ensure subsequent film coating, packaging, and preservation and transportation of the products.

[0115] Example 11 (Structural Characterization and Mechanism Verification)

[0116] Systematic structural characterization was carried out on Samples 1-3 to verify the microscopic characteristics and embedding mechanism of the microcapsule powder:

[0117] 1. Define the structural characteristics

[0118] Observed by scanning electron microscopy (SEM) (as Figures 1-3 ), the microcapsule powder presents an oval spherical or nearly jujube pit morphology, with uniform shrinkage on the surface. The D90 of the primary shell is 6.0 μm (Sample 1), 4.0 μm (Sample 2), 15.0 μm (Sample 3), and the D90 of the secondary shell is 36.0 μm (Sample 1), 31.0 μm (Sample 2), 39.0 μm (Sample 3), forming a multi-core embedding structure, which is consistent with the D50 / D90 / D99 data in Table 1.

[0119] 2. Wall material layer structure

[0120] The primary shell wall material is formed by complex coacervation of fish gelatin - gum arabic (Sample 1), bovine gelatin - sodium carboxymethylcellulose (Sample 2), and soy protein - sodium alginate (Sample 3). The same wall material combination is used for the secondary shell. The preferred molecular weight range (50-250 kDa) in Example 7 ensures the integrity of the interfacial film.

[0121] 3. Internal structure and component distribution

[0122] Through the step-by-step acidification coagulation process (Examples 1-3), the lipophilic core material (DHA, flaxseed oil, resveratrol) is preferentially encapsulated in the primary shell ( Figures 1-3 dark area), the hydrophilic / amphiphilic core material (ascorbic acid, krill oil, rapeseed oil diglyceride) is concentrated in the secondary shell ( Figures 1-3 Light-colored annular band) to achieve spatial isolation of core materials with different polarities.

[0123] 4. Additive location

[0124] After the mixed tocopherols (sample 1), antioxidant 264 (sample 2), and rosemary extract (sample 3) were premixed with the core material, their oxidation inhibition effect was verified by the accelerated test in Table 2, and the peroxide value increased by ≤6.9meq / kg, confirming that the antioxidants were effectively distributed at the active sites.

[0125] 5. Pore structure

[0126] like Figure 4 and 5 The SEM image shows that the structure of the outer wall material is dense after complex coagulation, which together with the low degradation rate (≤4.9%) in Example 5 verifies the barrier performance.

[0127] 6. Interface Features

[0128] In Example 6, when the primary shell D90 was 4-15 μm, the surface oil was ≤2% (Table 3). Combined with the pH control steps of Examples 1-3, the stability of the interfacial film dominated by electrostatic interactions was demonstrated.

[0129] In summary, the microstructures of samples 1-3 were systematically characterized:

[0130] 1. Multi-layer shell structure

[0131] As attached Figures 1-3 As shown, the microcapsule powder has a double-layer complex coacervate shell, including:

[0132] Primary shell layer: formed by protein-polysaccharide complex coagulation (fish gelatin-arabic gum / bovine gelatin-sodium carboxymethyl cellulose / soy protein-sodium alginate), with a thickness of 20-30% of the D90 value of the primary shell layer (corresponding to 1.2-4.5 μm), preferably with a molecular weight range of 50-250 kDa (supported by the data of Example 7);

[0133] Secondary shell: epitaxially grown on the primary shell by secondary acidification condensation, with a thickness of 10-15% of the D90 value of the secondary shell (corresponding to 3.1-5.9 μm);

[0134] Structural parameters:

[0135] Primary shell D90: 4-15 μm (data in Table 1);

[0136] Secondary shell D90: 31 - 39 μm (data in Table 1);

[0137] Total particle size D50 / D90 / D99: 21.3 - 27.6 μm / 31.2 - 39.0 μm / 64.0 - 94.2 μm (Table 1);

[0138] 2. Dense barrier performance

[0139] As shown in Figure 4 (SEM image of Example 1), the outer wall material presents a dense structure without pores (surface shrinkage rate > 85%);

[0140] Combined with:

[0141] Peroxide value ≤ 6.9 meq / kg in the accelerated experiment (Table 2);

[0142] Surface oil content ≤ 2% (Table 1);

[0143] It is proved that this structure effectively blocks the penetration of moisture / oxygen and realizes the function of the physical barrier.

[0144] 3. Spatial distribution of multi-polar core materials

[0145] Through the stepwise embedding process (Examples 1 - 3):

[0146] Lipophilic core materials (DHA, linseed oil, resveratrol) are preferentially located inside the primary shell ( Figures 1-3 dark core area);

[0147] Hydrophilic / amphiphilic core materials (ascorbic acid, krill oil, rapeseed oil diglyceride) are enriched in the periphery of the secondary shell ( Figures 1-3 light-colored annular zone);

[0148] Realize the physical isolation and embedding of components with different polarities, showing significant differences from the "porous double-layer capsule wall" structure in the comparative document CN207204054U (the present invention is a dense and pore-free multi-layer structure).

[0149] 4. Interface stability mechanism

[0150] Electrostatic complex coacervation: By adjusting the pH (4.4 - 5.1) in Examples 1 - 3, proteins (positive charges) and polysaccharides (negative charges)

[0151] are electrostatically combined.

[0152] Verification of mechanical strength: When the primary shell D90 is 4 - 15 μm, the surface oil ≤ 2% (data in Example 6), proving the stability of the interfacial film.

[0153] As described above, it is only the preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.

Claims

1. A formulation of double-embedded microcapsule powder, characterized in that: It comprises the following components in parts by weight: 5 - 60 parts of core material in Group A, 5 - 40 parts of core material in Group B, 5 - 16 parts by weight of protein-based wall material, 3 - 19 parts by weight of polysaccharide-based wall material, 0.1 - 2 parts by weight of curing enzyme, 1 - 10 parts of filler, 1 - 4 parts of pH regulator, and 0 - 2 parts by weight of antioxidant.

2. The formulation according to claim 1, wherein: The core material in Group A is selected from lipophilic core materials, amphiphilic core materials or amphoteric-insoluble core materials; the core material in Group B is a hydrophilic core material, amphiphilic core material or amphoteric-insoluble core material.

3. The formulation according to claim 1, wherein: The lipophilic core material is selected from one or a mixture of several of vegetable oil, animal oil, Haematococcus pluvialis oil or fat-soluble vitamins; the hydrophilic core material is selected from one or a mixture of several of water-soluble vitamins and highly soluble amino acids; the amphiphilic core material is selected from one or a mixture of several of diglyceride oil, phospholipid oil and glycolipid oil; the amphoteric-insoluble core material is selected from one or a mixture of several of polyphenolic substances or amino acid substances with low solubility.

4. The formulation according to claim 1, wherein: The protein-based wall material is selected from one or a mixture of several of fish gelatin, pig gelatin, bovine gelatin, soy protein, pea protein, pumpkin protein, hemp protein, chickpea protein, barley protein; the molecular weight of the protein-based wall material is 50 - 250 kDa.

5. The formulation according to claim 1, wherein: The polysaccharide-based wall material is selected from one or a mixture of several of gum arabic, sodium alginate, alginate, chitosan, carrageenan, pectin, starch, modified starch, cellulose, methylcellulose, ethylcellulose, carboxymethylcellulose.

6. The formulation according to claim 1, wherein: The filler includes one or a mixture of several of glucose syrup, lactose, maltose, solid corn syrup, maltodextrin; the DE value of the filler is 40 - 70.

7. According to the formulation of claim 1, it is characterized in that: The antioxidant is selected from one or a mixture of several of d-α tocopherol, dl-α tocopherol, mixed tocopherols, rosemary extract, phospholipid, butylated hydroxyanisole, antioxidant 264, tertiary butyl hydroquinone.

8. A method for preparing microcapsule powder according to the formula as claimed in claim 1, comprising the following steps: (1) Dissolve the protein-based wall material fully in 50 - 150 parts by weight of water; (2) Dissolve the polysaccharide-based wall material fully in 30 - 190 parts by weight of water; (3) Mix the liquids prepared in steps (1) and (2) fully; (4) Add 0 - 1 part by weight of antioxidant to the core material in Group A and mix fully; (5) Mix 30 - 70% by weight of the liquid prepared in step (3) and the liquid prepared in step (4), and perform shear emulsification; (6) Add 0 - 1 part by weight of antioxidant to the core material in Group B; (7) Mix the remainder of the liquid prepared in step (3) and the liquid prepared in step (6), and perform shear emulsification; (8) Take the concentrated emulsion prepared in step (5), dilute it to a solid content of 4 - 7 wt%, then adjust the pH of the emulsion to 5.0 - 5.2, adjust the particle size D90 of the system to 2 - 20 μm, cool, add the curing enzyme for curing to form the first layer of multi-core microcapsules; inactivate the curing enzyme; the curing enzyme used is 50 - 60% of the total weight; (9) Take the concentrated emulsion prepared in step (7), pour it into the emulsion in step (8), adjust the pH to 4.4 - 4.5, adjust the particle size D90 of the system to 20 - 50 μm, cool, add the curing enzyme for curing to form the second layer of multi-core microcapsules; inactivate the curing enzyme; (10) Add the filler to (9), stir until completely dissolved, and then perform spray drying to obtain the final product; wherein the DE value of the filler is controlled at 40 - 70.

9. A microcapsule powder with double embedding for different polar core materials prepared by using the formula described in claim 1, characterized in that: It includes core materials in Group A and cores in Group B with different polarities; the particle size D90 of the first layer of multi-core microcapsules is 2 - 20 μm; the particle size D90 of the second layer of multi-core microcapsules is 20 - 50 μm.

10. The application of the microcapsule powder according to claim 9 in food or health products.

Citation Information

Patent Citations

  • Method for preparing vitamin A and vitamin E nano-sphere / microsphere double-embedding system

    CN101214219A

  • Falling derrick construction technology teaching simulator

    CN103117021A

  • Composite condensation product with double-embedding function as well as preparation method and application of composite condensation product

    CN112205628A

  • Double -deck cyst wall microcapsule of porous -type

    CN207204054U

  • Micro-fluidic chip for preparing micro-droplets with double embedding structures

    CN221310709U

Cited By

  • Active peptide composition for adjusting emotion and improving side effects of medicine

    CN121102435A